Pedagogical Strategy of Writing Paragraphs Using Edmodo to Enhance Writing Skill for EFL Students - Shanty Duwila (Journal of English Language Teaching and Islamic Integration, 2019)
In today's digital era, there are a number of social media that can be used as a tool to help writing skills for those who learn English. One of the media is "Edmodo". Edmodo is a social networking based learning platform that is intended for teachers, students and parents. In this study, the researcher integrated Process and Genre-Based Approaches with Edmodo as a teaching strategy. The participants are the students from the 2nd semester of English Language Program at Wijaya Putra University. The procedure for developing the model applied in this study consisted of: planning, implementing, observing, and reflecting. The research found that 70% of the students support to use Edmodo in writing class while 30% of them gave a neutral opinion. Edmodo as an online media supports the effectiveness of the teaching learning process that is proved by the improvement of the students’ writing skill in which their scores increase dramatically. The main barriers of the use of Edmodo is incompatibility of their smartphone applications and confusion of using the application.